Exploration of Climate Literacy Level of High School Students In Prospective New Capital City of Indonesia - Abdul Hakim; Shelly Efwinda; Puardmi Damayanti; Tyas Renanda Nurtasya (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
Climate change in the 21st century has become the primary concern of all the countries' leaders, including Indonesia. In education, learning related to climate change needs special attention not only on the knowledge aspect but also on the attitudes and behavior of students. East Kalimantan is one of the provinces in Indonesia, and the Indonesian government does expect it to be the new nation's capital. This research is descriptive analysis research. This research aims to determine students' level of climate literacy in aspects of basic knowledge, attitudes, and behavior. The survey does conduct on 240 students of grade 12th students from eight different schools in East Kalimantan, Indonesia. The sampling technique is stratified random sampling. The research instrument used was a questionnaire divided into three aspects: basic knowledge, attitudes, and behavior. In the basic knowledge aspect, the questionnaire consists of 15 questions with a Guttman scale (true-false). Each questionnaire consists of 10 statements with a Likert scale in attitude and behavior. The results showed that students' level of climate literacy in the basic knowledge aspect was only in the sufficient category, and the attitude and behavior aspects were in the high category. Although, in general, the level of student climate literacy in the aspects of attitude and behavior is in the high category, there are still some students classified at the low level. We conclude that students' climate literacy still needs to be improved in terms of basic knowledge and aspects of attitude and behavior to prevent the future negative impacts of climate change.